2016
DOI: 10.3389/fpsyt.2016.00121
|View full text |Cite
|
Sign up to set email alerts
|

Can Interoception Improve the Pragmatic Search for Biomarkers in Psychiatry?

Abstract: Disrupted interoception is a prominent feature of the diagnostic classification of several psychiatric disorders. However, progress in understanding the interoceptive basis of these disorders has been incremental, and the application of interoception in clinical treatment is currently limited to panic disorder. To examine the degree to which the scientific community has recognized interoception as a construct of interest, we identified and individually screened all articles published in the English language on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(258 citation statements)
references
References 263 publications
(283 reference statements)
4
244
1
9
Order By: Relevance
“…The insula, associated with interoceptive processing and the processing of one's own bodily symptoms, plays an important role in panic disorder. 9,37,38 Hyperactivation in the anterior insula in our patients is best explained by fear of cardiovascular symptoms. Earlier studies found anxiety severity to correlate positively with insula hyperactivation in response to masked fearful faces in healthy controls and with insula activation in patients with panic disorder during emotional processing of facial affect expressions.…”
Section: Discussionmentioning
confidence: 99%
“…The insula, associated with interoceptive processing and the processing of one's own bodily symptoms, plays an important role in panic disorder. 9,37,38 Hyperactivation in the anterior insula in our patients is best explained by fear of cardiovascular symptoms. Earlier studies found anxiety severity to correlate positively with insula hyperactivation in response to masked fearful faces in healthy controls and with insula activation in patients with panic disorder during emotional processing of facial affect expressions.…”
Section: Discussionmentioning
confidence: 99%
“…First, it should be acknowledged that various theorists offer competing definitions of “interoceptive awareness” [5,7,10,11], yet this study drew upon an operationalization of interoceptive awareness consistent with belief in one’s interoceptive tendencies (Mehling, c.f. interoceptive sensibility as discussed in Garfinkel).…”
Section: Discussionmentioning
confidence: 99%
“…Despite pockets of convergence, the language of interoception continues to evolve and the discussion about the terminology remains ongoing [5,911]. Khalsa and Lapidus [10] provide a detailed review of operational alternatives, identifying 10 distinct definitions of interoception. In an effort to promote conceptual and operational synthesis, Garfinkel et al [9,11] offered and investigated a three-dimensional model of interoception, including interoceptive accuracy (accuracy in detecting bodily sensations, such as heartbeats), interoceptive sensibility (self-reported beliefs about interoceptive tendencies), and interoceptive awareness (“metacognitive awareness of interoceptive accuracy”, p.67) [11].…”
Section: Interoceptive Awareness and Psychological Well-beingmentioning
confidence: 99%
“…Most importantly, interoceptive accuracy is still considered one of the major factors contributing to the development and maintenance of panic disorder (80). …”
Section: Discussionmentioning
confidence: 99%